Pengembangan Perangkat Praktikum Local Material Untuk Meningkatkan Penguasaan Konsep Dan Aktivitas Belajar Siswa Pada Pembelajaran Cara Hidup Manusia, Hewan, Dan Tumbuhan Di Sekolah Dasar - Tyas, Arie Rahmaning; Hindriana, Anna Fitri; Sulistyono, Sulistyono (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2023)
This study aims to gain an overview of the product characteristics of the development of Local Material practicum tools in elementary schools, which can help improve students' mastery of concepts and learning activities in learning how to live humans, animals and plants in elementary schools. The emergence of this goal was motivated by the lack of practicum tools in elementary schools, so that it became an obstacle when they wanted to do practicum. This study used a research and development (R&D) approach covering the stages of curriculum analysis and observation, product design, design validation, design improvement, small-scale trials, and usage trials. The usage trial used Quasi-experiments. The research participants were fifth-graders at SDN Indrajaya 01, 02, 03, and 04, a four-school elementary complex in Indrajaya, Salem District, Brebes Regency. The results showed that the use of Local Material practicum tools can help improve students' mastery of concepts and learning activities. The product is suitable for use where, according to student responses, after a small-scale trial is carried out, it receives a score of 3.04 on the Eligible criteria and the teacher's assessment with an average score of 3.22 on the Eligible criteria. The effective product improves conceptual understanding, with tcount = 2.77 > from ttable 1.69 at a significant level of 5%. Effective products increase student activity with a score of 88.80 in the experimental class and 76.69 in the control class. The results showed that the product development of Local Material practicum tools can help improve students' mastery of concepts and learning activities.